Structural Applications of Malaysian Bamboos - Yap, Chee Lin (1987)
This experimental study to determine the structural applications of Malaysian bamboo is divided into three main parts namely a study on the physical and mechanical properties of three selected species of Malaysian bamboo, testing of four types of bamboo connectors, and testing of two mono-pitch trusses. It was found that the physical and mechanical properties of Malaysian bamboo tested are similar to those of light hardwood. Based on the strength properties obtained, it can be concluded that the bamboo species selected are suitable for use in construction. For the species tested, the Gigantochloa levis species was found to be the strongest, followed by the Dendrocalamus asper and Bambusa blumeana species. Of the four bamboo connectors tested, it was found that the boltedplywood bamboo connector showed better strength results. The other types of bamboo connectors tested suffered considerable slip at the joints. It was also found that the mono-pitch bamboo truss is of sufficient strength to be utilised for home construction. A spacing of up to two metres could be used if the trusses are to carry a corrugated asbestos roof over a span of 4.5 metres.